Integrating Sugar Metabolism With Transport: Elevation of Endogenous Cell Wall Invertase Activity Up-Regulates SlHT2 and SlSWEET12c Expression for Early Fruit Development in Tomato - Ru, Lei; He, Yong; Zhu, Zhujun; Patrick, John W.; Ruan, Yong-Ling (Frontiers in Genetics, 2020)
Early fruit development is critical for determining crop yield. Cell wall invertase (CWIN) and sugar transporters both play important roles in carbon allocation and plant development. However, there is little information about the relationship between CWIN and those functionally related sugar transporters during fruit development. By using transgenic tomato with an elevated CWIN activity, we investigated how an increase in CWIN activity may regulate the expression of sugar transporter genes during fruit development. Our analyses indicate that CWIN activity may be under tight regulation by multiple regulators, including two invertase inhibitors and one defective CWIN in tomato ovaries prior to anthesis. Among the sugar transporters, expression of SlSWEET12c for sucrose efflux and SlHT2 for hexose uptake were enhanced by the elevated CWIN activity at 10 and 15 daa respectively, of fruit development. The findings show that some specific SWEET and HT respond to elevate CWIN activity probably to promote rapid fruit expansion when sucrose efflux from phloem and hexose uptake by parenchyma cell are in high demand. The analyses provide new leads for improving crop yield by manipulating CWIN-responsive sugar transporters, together with CWIN itself to enhance fruit development and sugar accumulation